Perceptual responses proximal to the onset of blood lactate accumulation - Acevedo, E. O.; Kraemer, R. R.; Haltom, R. W. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: Running at incremental velocities proximal to the onset of blood lactate accumulation (OBLA) elicits linear increases in VO2, and HR, while the increases in VE and blood lactic acid concentrations (BLa) are curvilinear. In addition, effort sense is often measured in the field with the traditional 15-point scale Ratings of Perceived Exertion scale, increases linearly whereas the perceptual response of affect seem to decrease in a nonlinear manner. This study examined the changes in effort sense (RPE) and affect, utilizing the Feeling Scale (FS), at 3 running intensities proximal to the onset of blood lactate accumulation. In addition, the relationship between these perceptual responses and VE, VO2, HR, RER, and BLa were examined. Methods: Eleven highly-trained distance runners (VO2max = 67.65±1.24) participated in 2 sessions of data collection. During Session 1 subjects performed a discontinuous progressive treadmill protocol to determine peak aerobic power. After each stage a finger tip blood sample was taken to determine BLa. A regression line between the 2 successive workloads that produced BLa above and below 4 mM was calculated to predict the VO2 that would generate 4mM BLa (VO2 @ 4 mM). Within 1 week each subject returned for Session 2, which included a 10-min warm-up run followed by 3 submaximal runs lasting 5 min each: the VO2 at 10% below OBLA (VO2 10% inf , the VO2 at OBLA (VO2 @ 4 mM), and the VO2 at 10% above OBLA (VO2 10%). During the last minute of each run VO2, VE, HR, RER, RPE, and FS were assessed. In addition, Bla was assessed immediately following each run. Results: Results demonstrated that VO2 10% inf, VO2 @ 4 mM, and VO2 10% sup elicited BLa of 2.66±0.33, 3.75±0.40, and 6.10±0.68 mM, respectively. In addition, RPE increased significantly from VVO2 10% inf to VO2 @ 4 mM and from VO2 @ 4 mM to VO2 10% sup; whereas FS demonstrated a slight decrease from VO2 10% inf to VO2 @ 4 mM, and a more substantial and significant decrease from VO2 @ 4 mM to VO2 10% sup. Correlational analyses revealed significant relationships at VO2 10% sup. Specifically, RPE and FS were negatively related (r=0.62), while RPE and VO2 were positively related (r=0.53). Correlations across all workloads revealed a tendency for more powerful relationships to exist among RPE and physiological cues than FS and physiological cues. Conclusion: This is the first study to directly examine changes in RPE and FS in relation to the physiological threshold for anaerobic metabolism, Bla, which responds to linear increases in exercise intensity in a curvilinear manner. Results support previous investigations suggesting a that the drop in FS has some distinction from the increase in RPE and that FS may be more sensitive to the onset of anaerobic metabolism. Moreover, the relationship of RPE to FS at VO2 10% sup, but not VO2 10% sup and VO2 @ 4 mM, supports the hypothesis that the unique variability of FS is diminished at higher intensities of exercise when physiological cues are unambiguous.